Calila : The Later Novels of Carmen Martín Gaite - Brown, Joan Lipman (Book collections on Project MUSE., 2021)
"Calila: The Later Novels of Carmen Martín Gaite explores the last six novels by Spain's most honored contemporary woman writer. Its scholarship is enriched by the voice of Calila herself-as Brown called Martín Gaite, who was a dear friend-as they conversed and exchanged letters during the composition of the novels. The book opens with an introduction to Martín Gaite's life and literature and ends with a consideration of her legacy. Each central chapter analyzes a later novel in its historical, biographical, and critical contexts. From the young adult fantasy Caperucita en Manhattan (Red Riding Hood in Manhattan) to the post-Transition epistolary masterpiece Nubosidad variable (Variable Cloud), the Transition-era saga La Reina de las Nieves (The Farewell Angel), the Proustian reminiscence Lo raro es vivir (Living's the Strange Thing), the narrative tapestry Irse de casa (Leaving Home), and the memoir of family secrets Los parentescos (Family Relations), these fascinating novels evoke themes that resonate today"--